2020
DOI: 10.1002/ese3.772
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and fractal analyses of the mechanical properties and fracture modes of bedding‐containing shale under different seepage pressures

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…β denotes the average of the parameters of the physical properties of the primitive, m indicates the nature parameter of the distribution function, whose physical meaning reflects the homogeneity of the material medium, defined as the homogeneity coefficient of the material medium, reflecting the degree of homogeneity of the material, f(x) is the density of the statistical distribution of the physical properties x of the material (rock) primitive. The material parameters in this test are derived from the mechanical parameters of shale in the Lower Cambrian Niutitang Formation in north area of Guizhou (Wu et al, 2020), and are summarized in Table 1, where the values in brackets represent the uniformity coefficient of this parameter. The elastic modulus diagram after the assignment is shown in Figure 5D.…”
Section: Shale 3d Model Reconstructionmentioning
confidence: 99%
“…β denotes the average of the parameters of the physical properties of the primitive, m indicates the nature parameter of the distribution function, whose physical meaning reflects the homogeneity of the material medium, defined as the homogeneity coefficient of the material medium, reflecting the degree of homogeneity of the material, f(x) is the density of the statistical distribution of the physical properties x of the material (rock) primitive. The material parameters in this test are derived from the mechanical parameters of shale in the Lower Cambrian Niutitang Formation in north area of Guizhou (Wu et al, 2020), and are summarized in Table 1, where the values in brackets represent the uniformity coefficient of this parameter. The elastic modulus diagram after the assignment is shown in Figure 5D.…”
Section: Shale 3d Model Reconstructionmentioning
confidence: 99%
“…In Eq. 1, the mechanical property parameters of the unit are characterized by α, such as the modulus of elasticity and compressive strength, where α0 characterizes the average value of the mechanical property parameters for the unit and m Frontiers in Earth Science frontiersin.org characterizes the homogeneity of the material; the more homogeneous the material, the larger the m. According to the literature (Zhu et al, 2011;Lou et al, 2020;Wu et al, 2020), each known mechanical parameter for the shale is shown in Table 1. In order to study the mechanical properties, rupture process and acoustic emission signal evolution characteristics of shale containing different inclination angles of natural cracks at microscopic scale, so as to establish numerical models of shale specimens with internal natural crack inclination angles of 0 °, 15 °, 30 °, 45 °, 60 °, 75 °, 90 °and control group without natural cracks under uniaxial compression conditions, a total of 8 groups, were tested numerically by RFPA2D-DIP, and the mechanical loading model is shown in Figure 7, loaded by displacement control volume.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Figure 8 is a numerical model obtained by converting an image after digital image processing. The material parameters of the micromedia in the shale are shown in Table 1 [39].…”
Section: Establishment Of the Numerical Modelmentioning
confidence: 99%